Effectiveness of Baby Massage on Weight Infants Aged 7-12 Months - Simanjuntak, Lusi Ferawati; Dinengsih, Sri (Jurnal MIDPRO, 2023)
Growth and development babies depend a lot on fulfillment nutrition. A number of frequent problem happen in fulfillment nutrition difficulty eat what you can cause happening disturbance growth in babies. Prevalence difficulty eat of 33.6%, 44.5% of them suffer malnutrition light until moderate and 79.2 % of subject study has experience difficulty eat more than 3 months (Rikesda, 2018). Baby massage can increase absorption food so that baby more fast hungry and baby will more often suckle. This research aim to know influence baby massage to baby 's weight at 7-12 months on groups treatment and control. This research use quantitative study quasi experiment with design two group pretest- posttest design. Which consists of 30 infants aged 7-12 months that consisted of 15 as group intervention and 15 as group control. Retrieval technique  sample use  purposive sampling technique. Data analyzed using paired t-test and Independent-test. On research this obtained mark significance test results paired T-Test of 0.000 (P=0.000<0.05). Can concluded that is influence baby weight after  done  massage. Research results expected can increase mother 's knowledge about importance massage baby for increase baby weight.